Learners' attitudes to mixed-attainment grouping: examining the views of students of high, middle and low attainment. Issue 4 (4th July 2019) - Tereshchenko, Antonina; Francis, Becky; Archer, Louise; Hodgen, Jeremy; Mazenod, Anna; Taylor, Becky; Pepper, David; Travers, Mary-Claire
Abstract: There is a substantial international literature around the impact of different types of grouping by attainment on the academic and personal outcomes of students. This literature, however, is sparse in student voices, especially in relation to mixed-attainment practices. Research has indicated that students of different attainment levels might have different experiences and views of grouping structures. This paper represents a significant contribution to this literature. Drawing on the data collected as part of a large study on student grouping and teaching in England, we analyse the attitudes of students of different attainment levels to mixed-attainment practice, focusing on their explanations for their preferences or aversion to mixed-attainment classes. The data-set is drawn from group discussions and individual interviews with 89 students age 11/12 (Year 7) from eight secondary schools practicing mixed-attainment grouping in mathematics and English. Our analysis identifies some broad patterns in student attitudes, including a strong preference for mixed attainment among those at lower prior attainment. The analysis of the explanations students give for their opinions on mixed-attainment practice demonstrates how the learner identities of different groups of students are constituted in various ways by the discourses around 'ability', and constrained by the dominant ideology of 'ability' hierarchy.